2010
DOI: 10.1590/s1519-566x2010000400023
|View full text |Cite
|
Sign up to set email alerts
|

Estudios biológicos de Trichogrammatoidea bactrae Nagaraja (Hymenoptera: Trichogrammatidae), parasitoide de huevos de Tuta absoluta Meyrick (Lepidoptera: Gelechiidae)

Abstract: -The tomato moth, Tuta absoluta Meyrick, is one of the most important tomato pests in South America. In Argentina, management strategies include only chemical control. In this work, the parasitoid wasp Trichogrammatoidea bactrae Nagaraja was evaluated as a potential natural enemy against this pest. Biological and population parameters were estimated by developing a life table under laboratory conditions at 25 ± 1ºC, 14:10 photoperiod and 60 ± 10% RH. Three cohorts of 26-30 T. bactrae females each were placed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 17 publications
0
8
0
1
Order By: Relevance
“…The longevity of T. bactrae varied from 1-15 days with mean longevity of 7.9±0.37 days, when fed on 50 % bees honey. Longevity was 6.2 on T. absoluta and 6.1 d on S. cerealla (Virgala and Botto, 2010). Longevity of T. bactrae is comparatively shorter than in other egg parasitoid species.…”
Section: Assessment Of the Longevity Of T Bactraementioning
confidence: 79%
See 1 more Smart Citation
“…The longevity of T. bactrae varied from 1-15 days with mean longevity of 7.9±0.37 days, when fed on 50 % bees honey. Longevity was 6.2 on T. absoluta and 6.1 d on S. cerealla (Virgala and Botto, 2010). Longevity of T. bactrae is comparatively shorter than in other egg parasitoid species.…”
Section: Assessment Of the Longevity Of T Bactraementioning
confidence: 79%
“…Fecundity of T. bactrae could change with the type of host eggs. Fecundity of T. bactrae was 48.9 eggs/female when T. absoluta was used and 39 when S. cereallela was used as the host (Virgala and Botto, 2010). T. bactrae shows lower fecundity compared with other trichogrammatid egg parasitoid species.…”
Section: Assessment Of the Fecundity Of T Bactraementioning
confidence: 88%
“…bactrae on an invasive pest, T. absoulta in an open tomato fields. These species are mainly used in biological control of T. absoluta in the South American and European countries (Cabello et al, 2009;Virgala and Botto, 2010). The emergence of T. achaeae and Tr.…”
Section: Resultsmentioning
confidence: 99%
“…A recent paper 44 showed that the predation rates of nymphs and adults of the damsel bug Nabis pseudoferus Remane (Hemiptera: Nabidae) are similar to those of mirid predators, but the paper contained insufficient information to be able to calculate the pest kill rate. 50 , an exotic species initially introduced into Argentina for control of Pectinophora gossypiella Saunders (Lepidoptera: Gelechiidae) 45,50 . In South America, most studies on larval parasitoids of T. absoluta concern D. phthorimaea, Dolichogenidea (Apanteles) gelechiidivoris Marsh.…”
Section: Methodsmentioning
confidence: 99%